Family and Local Elites as a Social Control for Children Deviation in Sungaiselan Village Central Bangka District - Ismi Nofiani Nurfadilla (Green Publisher Indonesia, 2021)
Deviant behavior can be defined as behavior that violates or iscontrary to the normative rules of the social environment concerned.Deviation is often done by adolescents to adults, but nowadayschildren also often do it. Sungaiselan Atas Village is one of the areaswhere children often perform deviant behaviors for children of theirage, namely drinking alcohol and gluing. The purpose of this studywas to identify the causes of children in Sungaiselan Village to deviateand to determine the social control of the family and local elites ofSungaiselan Village in overcoming children's behavior. This studyuses Containment Theory from Walter C. Reckless. The method usedin this research is descriptive qualitative. The data sources of thisresearch are divided into two, namely primary data sources andsecondary data sources. The data analysis techniques used byresearchers were data reduction, data display, and conclusiondrawing. The results of this study found that the factors that causechildren to deviate are lack of attention from their parents, lots of freetime, and a friendly environment. In addition, social control from thefamily and local village elites was also found, namely repressive andpreventive measures.